A Gateway-Centered Workflow Rollback Decision Model Toward Autonomous Workflow Process Recovery - Ahn, Hyun; Kim, Kwanghoon Pio (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
In enacting a workflow process model, it is very important to control and trace each instance’s execution as well as to keep it recoverable. Especially, the recoverability issue implies that the underlying workflow management system is able to not only provide an automatic error-detection functionality on its running exceptions but also to equip a very autonomous recovery mechanism to deal with the detected exceptional and risky situations. As a theoretical approach to resolve the autonomous workflow recovery issue, this paper tries to formalize a rollback-point decision tree structure based upon gateway-activities of a corresponding workflow process model, which is named as a gateway-centered workflow rollback decision model. We strongly believe that the proposed model ought be one of those impeccable trials and pioneering contributions to improve and advance the capability of recovery in enacting workflow process models.